Rancang Bangun Sistem Informasi Helpdesk Berbasis website di Rumah Sakit Harapan Keluarga Cipacing - Gilang Winara; Tonton Taufik Rachman (Jurnal Dimamu, 2023)
This hospital receives complaints and complaints from patients through the hospital's telephone number, which is not conducive because it is not properly and accurately recorded. So that reports on patient complaints are not conveyed to superiors or the hospital. As for the delays in the process of finding complaint data by officers who have submitted it from patients. The purpose of creating this helpdesk system is to make it easier for hospital staff to handle questions or complaints from patients and to record all helpdesk activities in a systematic manner and can be reviewed again for specific needs such as assessments, problems that often occur and solutions for each incident that occurs. The analysis carried out in this study includes an analysis of the currently running system and an analysis of the proposed system. The system design used is the OOAD (Object Oriented Analysis and Design) method approach with the UML (Unified Modeling Language) programming language. The design of this information system is expected to make it easier for hospital staff to respond to helpdesk services submitted by patients, present helpdesk service information anywhere and anytime, and minimize long queues that may occur.